Combining the Copenhagen Adduction Exercise and Nordic Hamstring Exercise improves dynamic balance among male athletes: A randomized controlled trial - Al Attar, W. S. A.; Faude, O.; Husain, M. A.; Soomro, N.; Sanders, R. H. (Sports Health: A Multidisciplinary Approach, 2021)
Background: Copenhagen adduction exercise (CAE) and Nordic hamstring exercise (NHE) reduce the incidence of groin and hamstring injuries. Efficient dynamic balance can improve motor performance and reduce the risk of injuries in athletes. However, the effects of these exercises on dynamic balance have not been investigated. Hypothesis: CAE and NHE, as well as a combination of both exercises, would improve dynamic balance among amateur male athletes. Study Design: Randomized controlled trial. Level of Evidence: Level 1. Methods: A total of 200 male athletes aged 21.9 ± 2.4 years were included in the study and randomly assigned to 4 groups: CAE group (n = 50), NHE group (n = 50), CAE and NHE group (n = 50), and a control group (n = 50). A total of 177 male athletes completed the study. The primary outcome measure was the limit of stability (LoS), which was measured using the Biodex Stability System to assess the performance of the dynamic balance. The LoS of the athletes` performance was measured pre- and postintervention after 6 weeks. Results: The LoS significantly improved in all treatment groups, including CAE (44.5% ± 5.3%), NHE (43.2% ± 5.3%), and CAE + NHE (48.4% ± 5.1%) groups when compared with the control group (28.3% ± 4.8%) after 6 weeks (all Ps < 0.01). The improvement of LoS was significantly greater in the CAE + NHE group compared with other groups (CAE, NHE, and control groups). Conclusion: There was a significant increase in dynamic balance performance postintervention among male athletes. CAE and NHE may improve injury prevention programs. Clinical Relevance: The results of this study provide evidence for athlete trainers and coaches to consider including the CAE and NHE as components of injury prevention programs to improve balance capacity and performance in athletes. Such improvements in balance may prevent injury risk and decrease absenteeism and injury-related financial burdens.